2007
DOI: 10.1002/sim.2806
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and maximizing coverage in the World Trade Center Health Registry

Abstract: The World Trade Center Health Registry (WTCHR) is a database for following people who were exposed to the disaster of 11 September 2001. Hundreds of thousands of people were exposed to the immense cloud of dust and debris, the indoor dust, the fumes from persistent fires, and the mental trauma of the terrorist attacks on the WTC on 9/11. The purpose of the WTCHR is to evaluate the potential short- and long-term physical and mental health effects of the disaster. The definitions of the exposed groups are broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 4 publications
0
87
1
Order By: Relevance
“…Extrapolating the prevalence of symptoms to the estimated 400 000 adults exposed to the WTC disaster, ∼25 000 experienced persistent LRS during the 12-month interval before W320 32 (see online supplementary appendix table S2). This generalisation, however, may be affected by study selection factors (see limitations below).…”
Section: Discussionmentioning
confidence: 99%
“…Extrapolating the prevalence of symptoms to the estimated 400 000 adults exposed to the WTC disaster, ∼25 000 experienced persistent LRS during the 12-month interval before W320 32 (see online supplementary appendix table S2). This generalisation, however, may be affected by study selection factors (see limitations below).…”
Section: Discussionmentioning
confidence: 99%
“…The methods and findings of W1 have been previously published. 4,7,9,11,12,25,27 The potential impact of selfselection bias in W1 registry enrollment has been described in other reports. Wave 1 studies examining either asthma or probable PTSD included subanalyses of list-identified participants to measure self-selection influences.…”
Section: Study Populationmentioning
confidence: 90%
“…25 Disease rates for self-and listidentified enrollees from W2 were multiplied by the respective estimated population exposed. To address potential selection bias attributable to the higher prevalence of disease among selfvs list-identified persons, the midpoint estimate was based on disease rates among list-identified enrollees only.…”
Section: Study Variablesmentioning
confidence: 99%
“…Details on Registry eligibility criteria, recruitment methods, and findings have been published elsewhere (Brackbill et al, 2009;Farfel et al, 2008;Murphy et al, 2007). In summary, Registry enrollees comprise rescue/recovery workers and volunteers; lower Manhattan residents; area workers; passers-by; and school children and staff.…”
Section: Data Sourcementioning
confidence: 99%